Sindbad, el marino - Abumalham, Montserrat (Revista de Filología Románica, 2006)
The most significant hero in sail’s storytelling of Arabic Literature is Sindbad, the sailor. This article undertakes a comparative analysis of the structure of all travels included in Thousand and one nights, paying attention to the functions the hero represents in front of basic elements of an initial travel.